Direct decoration of Co3O4/r-GO nanocomposite on nickel foam for electrochemical energy storage applications. Issue 7 (1st April 2021) - Aadil, Muhammad; Warsi, Muhammad Farooq; Agboola, Philips O.; Aly Aboud, Mohamed F.; Shakir, Imran
Abstract: Excellent electronic transport, fast ionic transport, and larger surface area are three fundamental requirements for electrode material to be suitable for advanced energy storage applications. Herein, a novel Co3 O4 /r-GO nanocomposite electrode material with higher specific capacitance (Csp), good rate capability, and excellent cycle performance has been prepared for electrochemical applications. The Co3 O4 /r-GO nanocomposite has deposited on the nickel foam (NF) via a single step in the situ hydrothermal routes. Benefiting from the excellent conductivity, higher specific surface area and electric double layer capacitance (EDLCs) of r-GO, the Co3 O4 /r-GO@NF electrode shows a higher Csp of 865 Fg -1 @ 1 Ag -1 . The Csp of the NF supported nanocomposite show a minimum capacity loss of 17.8% on increasing the applied current density from 1 to 7 Ag -1 revealing its good rate capability. Moreover, the Co3 O4 /r-GO@NF electrode also shows exceptional cycling stability with 93.2% Csp-retention after 5000 cycles. The exceptional capacitive performances are benefited from the nanostructured morphology, hybrid-composition, higher surface area (173.2 m 2 g -1 ), greater electrical conductivity (9.03 × 10 −3 Sm −1 ), and binder-free design of the prepared electrode material. All the achieved impressive electrochemical test's results prove that the Co3 O4 /r-GO@NF electrode is a very hopeful candidate as anode material for practical applications in the electrochemical capacitor. Graphical abstract: Image 1